Digital literacy and artificial intelligence literacy in teacher training - Rachbauer, Tamara; Graup, Johannes; Rutter, Eva (Forum for Education Studies, 2025)
The research titled “digital and AI literacy in teacher training” seeks to bolster the professional training of future educators in all phases of teacher education within Germany, with a particular emphasis on integrating digital and artificial intelligence (AI) literacy into contemporary educational practices. Recognizing the escalating importance of digital competencies—an urgency that the COVID-19 pandemic underscored globally—this initiative establishes a cohesive framework connecting universities, seminar leaders, and schools. Its core objective is to enable student teachers to adopt and implement digital methodologies in the classroom while providing continuous, contextually relevant training for in-service educators. Through this interconnected structure, the research aims to bridge educational theory and practice. Methods: The research applies a Design-Based Research (DBR) methodology, facilitating a dynamic process in which educational tools and approaches are developed, tested, and refined in real-world settings. To assess efficacy, the research utilizes online questionnaires aligned with established digital competence frameworks, such as the European DigCompEdu model, enabling educators at all stages of teacher training to self-assess their digital and AI literacy skills. The geographical context of Bavaria in southern Germany is specifically referenced, where the research pilot takes place to set a scalable example for broader implementation. Findings: Preliminary evaluations reveal that the module-based structure effectively enhances participants’ digital competencies. Teacher candidates report a higher degree of readiness to implement digital teaching tools, collaborate effectively online, and navigate AI-related resources in classroom contexts. This reflects an overall improvement in digital confidence and capability, particularly in areas like content creation and pedagogical communication. Conclusions: The research’s structured approach, fostering institutional collaboration and phased integration of digital competencies, highlights an effective model for embedding AI and digital literacy in teacher education. Continuous assessments and feedback loops ensure its relevance across training stages, enabling educators to remain adaptive and responsive to new educational technologies. Ultimately, this model may serve as a blueprint for other regions and countries aiming to update and enhance their teacher training frameworks in response to digital transformation demands.